G-CSF-Associated Bone Marrow Necrosis in AML after Induction Chemotherapy - Ikenna Osuorji; Lyle Goldman (Case Reports in Hematology)
Bone marrow necrosis (BMN) is defined as necrosis of the myeloid tissues and stroma without involvement of the cortical bone. We report a case of 66-year-old male with AML-M4 (FAB classification) who was given induction chemotherapy with cytarabine and daunorubicin. Filgrastim at 480 micrograms was administered on days 15–19 to shorten the duration of neutropenia. Consequently patient developed severe pelvic bone pain, leukoerythroblastosis, and severe leukocytosis. Repeat bone marrow aspiration and biopsy on day 21 confirmed bone marrow necrosis. These manifestations responded quickly to discontinuation of filgrastim. Subsequently, he recovered full myelopoiesis. We suggest that there may be more cases of BMN associated with G-CSF that are undiagnosed.